Impact of a heart failure multidisciplinary clinic on the reduction of healthcare-related events and costs: the GEstIC study - Rego, Rita; Pereira, Nuno; Pinto, António; Pereira, Sofia; Marques, Irene (Frontiers in Cardiovascular Medicine, 2023)
Introduction Heart failure (HF) is the leading cause of hospitalization in the elderly in developed countries and significantly impacts public health expenditures. Patients with HF usually have associated comorbidities that require multidisciplinary management. This study aims to demonstrate the benefits of a multidisciplinary clinic in reducing all-cause hospitalizations and HF events (HF hospitalizations and urgent HF visits) in a real-world setting. Finally, the study evaluates the associated costs of HF events. Methods This observational study included patients admitted to GEstIC, a multidisciplinary Portuguese HF clinic, from January 2013 to February 2019, who had one-year follow-up. Hospitalizations and HF events, total days spent in the hospital during HF hospitalizations, and HF events-related costs, in the year before and the year after GEstIC admission, were compared. Results Of the 487 patients admitted to the GEstIC, 287 were eligible for the study sample. After one year of HF patients' multidisciplinary management at GEstIC, there was a 53.7% reduction in all-cause hospitalizations (462 vs. 214), a 71.7% reduction in HF hospitalizations (392 vs. 111), and a 39.1% reduction in urgent HF visits (87 vs. 53). As a result, there was a significant decrease of 12.6 days in the length of hospital stay due to HF per patient (15.6 vs. 3.0, p < 0.001). This translated into the release of 9.9 hospital beds in the year following admission to GEstIC. The average total savings associated with the reduction of HF events was €5,439.77 per patient (6,774.15 vs. 1,334.38, p < 0.001), representing a total cost reduction of €1,561,213. Furthermore, the significant reduction in the number of all events was independent of the patient's left ventricular ejection fraction (LVEF). Discussion Significant reductions in all-cause and HF hospitalizations and urgent HF visits were observed with the implementation of this multidisciplinary clinic for HF patients' management. This was particularly important for patients with LVEF >40%. Before GEstIC, there was no medical intervention to improve the prognosis of these patients. The reduction of over one million euros in health-related costs after only one year of person-centered multidisciplinary management highlights the need to replicate this approach in other national healthcare institutions.